Organizational Culture and Innovation: A Meta‐Analytic Review1. Issue 4 (2nd April 2013) - Büschgens, Thorsten; Bausch, Andreas; Balkin, David B.
<x xml:space="preserve">Abstract</x> The relationship of organizational culture and innovation has been subject to extensive research over the last decades. The multitude of cultural variables under investigation has led to a fragmented concept of culture for innovation, and an inclusion into management theory is still missing. Further, managerial practice requires an underlying structure in order to decide what culture should be implemented in order to foster innovation, and to assess if a specific culture is an effective and efficient coordination instrument. Hence, a framework is needed which allows classification of cultural values without residuals, to draw expedient comparisons with reference to the criteria by which they are grouped, and to assess their relationship with organizational innovation. This meta‐analysis, which comprises 43 studies with a combined sample size of 6341 organizations, reveals that Quinn and Rohrbaugh's Competing Values Framework provides a meaningful structure for the ideational aspects of organizational culture. The Competing Values Framework describes value systems based on two main dimensions. Those two pairs of opposing values are flexibility versus control and internal versus external orientation. The analysis shows that the congruence of different cultures with organizational goals of innovation can be described based on that framework. Control theory is used to explain the relationship of organizational culture and innovation. While culture describes the ideational aspects of organizational values, clan control describes their coordinative effect. Managers may choose different clan control strategies according to the Competing Values Framework. They will most likely follow the strategy that provides a high level of congruence between the goals of management and the goals of their organization's social system. Individuals that have internalized the organizational values apply them as a form of self‐control. Those values will also be applied in groups, such as product development teams. While development teams may be formed and disbanded with certain projects and individuals may leave the company, the organization forms the steady frame of those activities. The cumulative data confirms the hypothesis that managers of innovative organizations most likely implement a developmental culture, which emphasizes an external and a flexibility orientation. Yet also group and rational cultures are to a certain extent consistent with the goals of an innovative organization and may thus be appropriate social control strategies. Hierarchical cultures emphasize control and an internal orientation and are less likely to be found in innovative organizations. A moderator analysis of the culture–innovation relationship revealed that it is not influenced by the differentiation between radical and incremental innovation, and only weak evidence exists for an influence of innovation adoption versus innovation generation. A potential reason is that those organizations that are geared toward innovation will pursue it consequently, without differentiating between different kinds of innovation. Therefore, managers that follow a (radical) innovation strategy should establish a developmental culture in their organization. If innovation rather represents a minor aspect of the firm's long‐term objectives, the efficiency‐oriented rational culture or a group culture may also be the right choice.